Law, ecology, and the management of complex systems : the case of water governance - Paloniity, Tiina, 1982- (Routledge, 2023)
"This book addresses the role of law in the adaptive management of socioecological systems. Recent years have witnessed a rise in discussion over the relation between adaptivity and law; as if after decades of insouciance, legal scholars have finally started to understand the impacts of the scientific paradigm called adaptive management to the legal sphere. Even though the complicated relations between law and the adaptive management of socioecological systems have become more debated, a thorough examination of the scientific and theoretical fundamentals of such endeavours has yet to be presented. Using the illustrative example of European Union water governance and its path towards embracing adaptive management, this book emphasises the legal significance of properly understanding the manner in which scientific knowledge of the environment is produced. Though always pivotal, rigorously apprehending science is especially crucial when dealing with the management of complex ecosystems as the 'normative' is created gradually before law begins to examine the 'facts' of the matter. After examining the roots of adaptive management, this book argues that the legal needs to understand itself as an integral part of the process of the socioecological management of complex systems, and not merely an external umpire resolving disputes. As whole the book offers new insights into the Union regulator's approaches to scientific realities, making it an interesting read not only to academics and legal scholars but also to regulators striving to deepen their understanding or pondering which approach to adopt in the face of new regulatory challenges, and to scientists interested in the science and law aspects of their work"-- Provided by publisher.
Based on author's thesis (doctoral - Helsingin yliopisto, 2018) issued under title: The (in)compatibility between adaptive management and law : regulating agricultural runoff in the EU.
Keywords: Runoff -- Law and legislation -- European Union countries.; Agricultural pollution -- Law and legislation -- European Union countries.; Water-supply -- Management.